(untitled) - Pant, Pushpesh (New Delhi, 2004)
Taken mainly from the South Asian Buddhist countries, these recipes provide a range of tastes and flavours that disprove the myth that vegetarian food is bland and unappetizing. From Buddhist Chinese and Japanese cooking styles that vary from steaming, stir-frying to grilling and baking, the sublime aromas of Indian cuisine, the creativity of Thai cuisine, the harmonious fusion of Sri Lankan and Indonesian food, to the rustic ruggedness of the basic Tibetan diet, the 50 recipes in this book offer a delectable array of peace foods. The author explains the philosophy that lies behind the middle path of the Buddha and how the right foods enhance mental peace and 'centre' your life. A practical guide to peace food.
Keywords: Cooking,Nấu các món chay,Nấu ăn,Vegeterian cooking; Religious aspects,Khía cạnh tôn giáo; Ấn Độ,India